2005
DOI: 10.1111/j.1365-2249.2005.02675.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of fractalkine (CX3CL1) and its receptor, CX3CR1, in periodontal diseased tissue

Abstract: SummaryThe regulatory role of chemokines and chemokine receptors on specific leucocyte recruitment into periodontal diseased tissue is poorly characterized. We observed that leucocytes infiltrating inflamed gingival tissue expressed marked levels of CX3CR1. In periodontal diseased tissue, the expression of fractalkine and CX3CR1 mRNA was detected by reverse transcriptionpolymerase chain reaction (RT-PCR) and further, fractalkine was distributed mainly on endothelial cells, as shown by immunohistochemistry. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 24 publications
1
49
2
1
Order By: Relevance
“…Single-strand cDNA for a PCR template was synthesized from 48 ng of total RNA using the oligo(dT) [12][13][14][15][16][17][18] primer (Invitrogen, Carlsbad, CA, USA) and superscript3 reverse transcriptase (Invitrogen) under the conditions indicated by the manufacturer. Specific primers were designed from cDNA sequences for gp130, OSM receptor beta (OSMRβ) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%
See 1 more Smart Citation
“…Single-strand cDNA for a PCR template was synthesized from 48 ng of total RNA using the oligo(dT) [12][13][14][15][16][17][18] primer (Invitrogen, Carlsbad, CA, USA) and superscript3 reverse transcriptase (Invitrogen) under the conditions indicated by the manufacturer. Specific primers were designed from cDNA sequences for gp130, OSM receptor beta (OSMRβ) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH).…”
Section: Rna Extraction and Reverse Transcription-polymerase Chain Rementioning
confidence: 99%
“…The disease initiation and progression result from the host response to plaque bacteria. Immunohistochemical studies have revealed dense inflammatory cell infiltration, including T and B cells and macrophages in periodontitis-affected regions [14][15][16][17][18][19]. Recently, several studies demonstrated that Th1 cells are involved in bone resorption in oral cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported that inflammatory cytokines and bacterial factors induced CX3CL1 in human vascular endothelial cells (HUVEC). Th1 cytokine, IFN‐γ enhanced CX3CL1 expression in HUVEC (Hatakeyama et al , 2004), while E. coli lipopolysaccharide and Porphyromonas gingivalis lipopolysaccharide significantly induced CX3CL1 production by HUVEC (Hosokawa et al , 2006). In the present study, CX3CL1 mRNA expression in both GT1 and RT7 cells was not induced by S. aureus, E. coli heat‐killed cells or TNF‐α (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The disease initiation and progression result from host response to plaque bacteria. Immunohistochemical studies revealed dense inflammatory cells infiltration, including T and B cells and macrophages in the periodontitis region [20][21][22][23][24][25]. Several studies demonstrated that Th1 cells are involved in bone resorption in oral cavity inflammation.…”
Section: Introductionmentioning
confidence: 99%